The clinical value of ultrasonic cardiac output monitor in very-low birth-weight and extremely-low-birth-weight infants undergoing PDA ligation. (February 2022) - Liu, Yu-Mei; Zheng, Man-Li; Sun, Xin; Chen, Xiao-Bo; Sun, Yun-Xia; Feng, Zhi-Chun; He, Shao-Ru
Abstract: Background: C ardiorespiratory instability occurs very often in very-low-birth-weight (VLBW) and extremely-low-birth-weight (ELBW) infants undergoing patent ductus arteriosus (PDA) ligation during the early postoperative period. This study aimed to investigate ultrasonic cardiac output monitor (USCOM) as a bedside tool by evaluating the hemodynamic changes in preterm infants following PDA ligation and assessing factors that may influence these changes. Methods: This was a single-center prospective observational study at a third-level neonatal intensive care unit. A total of 33 infants, including 21 VLBW and 12 ELBW infants, were involved. Hemodynamic measurements were performed in these infants using a USCOM preoperatively as well as 0–1 h, 8–10 h, and 24 h postoperatively. Results: The PDA ligation was associated with reductions of the left ventricular cardiac output (LVCO) ( P  < 0.001), cardiac index (P < 0.001), flow time corrected (FTC) ( P  < 0.001), Smith–Madigan inotropy index (SMII) (P < 0.001), oxygen delivery (DO2 ) ( P  < 0.001), and oxygen delivery index (DO2 I) (P < 0.001) and an increase of the systemic vascular resistance index (SVRI) (P < 0.001) at 0–1 h, 8–10 h, and 24 h post-ligation compared with the respective preoperative values. Compared with the respective values at 0–1 h post-ligation, there was no significant difference in the CI, SMII, or FTC at 8–10 h and 24 h post-ligation. However, the SVRI decreased at 8–10 h and 24 h post-ligation. Moreover, the DO2 I increased at 8–10 h and 24 h post-ligation, and the LVCO and DO2 increased at 24 h post-ligation. Conclusion: Our study confirmed that the hemodynamic changes measured by the USCOM were similar to those measured by echocardiography in previous reports. Thus, USCOM is a useful and convenient bedside tool for assessing hemodynamic changes to guide the use of fluids, inotropic agents, and vasopressors and help modify the post-ligation course, and they may be a surrogate for repeated echocardiography during the early post-ligation period in preterm infants or a preliminary screening method. Highlights: Evaluating the hemodynamic changes in preterm infants following PDA ligation and assessing the factors that may influence these changes The hemodynamic changes measured by USCOMs are similar to those measured by echocardiography in previous reports The postoperative course after PDA ligation may be modifiable, with hemodynamic monitoring by a USCOM guiding the use of fluid, inotropic agents, and vasopressors